2017
DOI: 10.22159/ajpcr.2017.v10i5.17189
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Niosomal Suspension of Cefixime

Abstract: Objectives: The present study was aimed to overcome the problems associated with the drug such as bioavailability, to reduce the dosage regimen, half-life, and to determine the appropriateness of niosomal formulation as a drug carrier. Methods:The niosomal suspension was prepared by thin film technique, by varying ratios of span 60 and cholesterol and varying the concentration of span 60. The prepared four formulations were evaluated for various parameters. Results:The optimized formulation had a vesicular siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Similar findings were reported by Kumar and coworkers presenting higher zone of inhibition with cephalosporin niosomes in contrast to the marketed formulation. 38 Thus, the CP proniosomes have been successfully obtained by this study is considered to be superior than conventional dosages owing to longer drug stay with controlled drug release and, improved stability and efficacy.…”
Section: Discussionmentioning
confidence: 88%
“…Similar findings were reported by Kumar and coworkers presenting higher zone of inhibition with cephalosporin niosomes in contrast to the marketed formulation. 38 Thus, the CP proniosomes have been successfully obtained by this study is considered to be superior than conventional dosages owing to longer drug stay with controlled drug release and, improved stability and efficacy.…”
Section: Discussionmentioning
confidence: 88%
“…The viscosity of alginate/HPMC mixtures affected the diameters and densities of beads and the volumes of entrapped drug substance. Alginate-chitosan beads increased in diameter with increasing chitosan concentrations, reflecting the formation of polyelectrolyte complexes between carboxyl groups of alginate and amine groups of chitosan [31][32][33][34]. Previous studies have shown that bead sizes are normally distributed over 50-2000 µm [35].…”
Section: Discussionmentioning
confidence: 95%
“…At low pressure, the rotatory evaporator was allowed to evaporate until a thin layer developed. The thin film was dried and dissolved in 20 mL of phosphate buffer, which was then placed in a water bath at 60ÂşC and rotated at 120 rpm to hydrate the layers [14,15,16,17].…”
Section: Methods Of Prepration Of Curcumin Niosomesmentioning
confidence: 99%